Fuzzy data management: Type 2 and Type 3 attributes in relational databases (Publicaciones en Ciencias y Tecnología, 2018)
The project "Challenges of the Fuzzy Relational Model" aims to solve open problems about the treatment of fuzzy data in relational databases. In the present work several results of this project are reported. Some concern with Type 2 fuzzy attributes, which are based on probability distributions. Others are on Type 3 fuzzy data, based on similarity relationships. One of the most emblematic results is a prototype of Database Management System for fuzzy data management. This prototype is called fuzzydoDB and consists of an extension to PostgreSQL. This extension supports queries with ordering and grouping on Type 2 and Type 3 fuzzy data. Additionally, a web portal also called fuzzydoDB is shown, whose purpose is to publicize the results of the project.
Keywords: fuzzy relational model; DBMS; fuzzydoDB; fuzzy data; fuzzy query; fuzzy